Resistive switching in HfO2-x/La0.67Sr0.33MnO3 heterostructures: an intriguing case of low H-field susceptibility of an E-field controlled active interface - Antad, Vivek; Shaikh, Parvez A.; Biswas, Abhijit; Rajput, Shatruhan Singh; Deo, Shrinivas; Shelke, V, Manjusha; Patil, Shivprasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2021)
High-performance nonvolatile resistive random access memories (ReRAMs) and their small stimuli control are of immense interest for high-speed computation and big-data processing in the emerging Internet of Things (IoT) arena. Here, we examine the resistive switching (RS) behavior in growth-controlled HfO2/La0.67Sr0.33MnO3 (LSMO) heterostructures and their tunability in a low magnetic field. It is demonstrated that oxygen-deficient HfO2 films show bipolar switching with a high on/off ratio, stable retention, as well as good endurance owing to the orthorhombic-rich phase constitution and charge (de)trapping-enabled Schottky-type conduction. Most importantly, we have demonstrated that RS can be tuned by a very low externally applied magnetic field (similar to 0-30 mT). Remarkably, application of a magnetic field of 30 mT causes RS to be fully quenched and frozen in the high resistive state (HRS) even after the removal of the magnetic field. However, the quenched state could be resurrected by applying a higher bias voltage than the one for initial switching. This is argued to be a consequence of the electronically and ionically ``active'' nature of the HfO2-x/LSMO interface on both sides and its susceptibility to the electric and low magnetic field effects. This result could pave the way for new designs of interface-engineered high-performance oxitronic ReRAM devices.
Keywords: charge trapping-detrapping; low external magnetic field; oxide-oxide interface; pulsed laser deposition; resistive switching; Schottky barrier

Review on recent progress in synthesis, properties, and applications of MXenes - Borah, Ashish Jyoti; Natu, Varun; Biswas, Abhijit; Srivastava, Anchal (Oxford Open Materials Science, 2025)
<h2 class="abstract-title js-splitscreen-abstract-title" id="540140110" scrollto-destination="540140110" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 1.5rem 1.2rem 0.9rem; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-stretch: inherit; font-size: 1.25rem; line-height: 1em; font-family: "Source Sans Pro", Helvetica, Arial, sans-serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline; background: rgb(239, 242, 247); color: rgb(42, 42, 42); margin-bottom: 0px !important;"> Abstract <section aria-label="Main abstract" class="abstract" style="box-sizing: border-box; margin: 0px; padding: 0px 1.2rem 1.7rem; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-stretch: inherit; font-size: medium; line-height: inherit; font-family: Merriweather, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline; position: relative; background: rgb(239, 242, 247); color: rgb(42, 42, 42);"> <p class="chapter-para" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: 15px; line-height: 1.7em; font-family: inherit; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline;"> MXenes, a noble class of two-dimensional (2D) material, discovered in 2011 have gained attention in recent years. They have attracted significant attention due to their flexible elemental composition, distinctive 2D-layered architecture, large surface area, and abundant surface terminations. Top-down synthesis techniques such as HF etching, alkaline etching, and electrochemical methods are used for MXene synthesis. Alongside these methods, methods like chemical vapor deposition (CVD), template method and plasma enhanced pulsed layer deposition (PELPD) are also used for the thin-film synthesis of MXenes. The discovery of double transition-metal layered MXene, solid, and high entropy MXene open up the prospect of further novel structures. MXenes are electrically conductive and have promising optoelectronic, mechanical, and thermoelectric properties. MXenes have also shown immense potential in biomedicine and environmental applications. The surface chemistry of MXene make them ideal for biosensors, drug delivery, and photothermal therapy, while their photocatalytic and adsorption properties enable efficient removal of pollutants and contaminants from water. This review examines the various MAX phase synthesis methods, such as solid-state reactions, hot isostatic pressing, and spark plasma sintering, followed by top-down techniques like HF etching, alkaline etching, and electrochemical etching, as well as bottom-up methods like CVD, template approaches, and plasma-enhanced pulsed layer deposition. The review also looks into the optical, chemical, and electronic properties of MXene, as well as their advancements in energy storage, optoelectronics, pollution avoidance, biomedical applications, and more.